Survey on the occurrence and diagnosis of fungal diseases of gerbera in Kerala - RESHMY VIJAYARAGHAVAN, N.M. PRAVEEN and (Indian Phytopathology, 2016)
Periodic sampling survey of diseases of Gerbera during the three seasons viz., July-August, November-December and March-April showed incidence of leaf blight, powdery mildew, root wilt and leaf spot diseases as major fungal diseases prevailing in Wayanad, Malappuram and Thrissur districts of Kerala. Per cent disease incidence and disease severity was recorded from the surveyed areas based on the different types of symptoms produced by different pathogens. Leaf blight and leaf spots were distributed commonly throughout all the districts compared to root rot and flower blight. The pathogens causing leaf blights were identified as Alternaria spp. and Myrothecium sp. and those causing leaf spots were identified as Curvularia sp. and Ulocladium sp. Phytophthora cryptogea and Fusarium solani were the pathogens causing root rots and wilts whereas Curvularia lunata caused petal blight. Morphologically distinct, two types of powdery mildew viz., Erysiphe sp. and Podosphaera sp. were identified during the study.